(En)visioning place‐based adaptation to sea‐level rise. Issue 2 (23rd November 2016) - O'Neill, Saffron J.; Graham, Sonia
Abstract : Sustainable climate change adaptation requires an understanding of people's place attachments, so that potential impacts and trade‐offs are illuminated when making adaptation decisions. Methods are needed that elucidate these important, but often intangible, place attachments at risk. A study was undertaken to explore place attachment, and how these person–place bonds might be impacted by flooding and sea‐level rise. It engaged with a small town in coastal Australia that is already highly vulnerable to flooding, and which has been subject to numerous policy directives intended to reduce climate change‐induced flood risk. The town therefore acts as an analogue for climate change adaptation in other semi‐rural coastal communities. Photo‐elicitation was found to be highly effective at elucidating multifarious dimensions of residents' place attachment. The attachments that were likely to be affected by flooding (and adapting to flood risk) were encapsulated in: the personal and communal identities associated with the tourism and fishing industries, the sense of belonging from living and re‐living family connections to local places, and the sense of community and enjoyment derived from diverse recreational activities. The photo‐elicitation process provided different outcomes to conventional interviews, focus groups and questionnaires. Participants sought to both vision (by elucidating their current experiences) and re‐envision (in advocating for different futures) their everyday experiences of adapting to flooding through their photographs and accompanying narratives. A video introduction to this paper is available at:https://vimeo.com/83484905 . Abstract : We demonstrate how participants used photo‐elicitation to both vision (by elucidating their current experiences) and re‐envision (in advocating for different futures) their everyday experiences of adapting to flooding and sea‐level rise through their photographs and accompanying narratives. We discuss what this means for carrying out climate adaptation policy and planning. e00028